A REVIEW OF PURCHASE INTENTION ON INSTAGRAM AMONG UNIVERSITI TEKNOLOGI MALAYSIA LOCAL UNDERGRADUATES’ STUDENTS - Nur Hafizah Zulkarnain; Sabrinah Adam, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The aim of this study to identify the conceptual framework of purchase intention on Instagram among local undergraduates’ students of Universiti Teknologi Malaysia (UTM). The variables consist of Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Web content as the independent variable, and purchase intention is the dependent variable. This study adopted a quantitative approach using IBM SPSS version 26. The survey was conducted on local undergraduates’ students at Universiti Teknologi Malaysia. The conceptual framework has been developed in this study. The expected findings show there is a positive relationship between Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Web content and purchase intention.